2020
DOI: 10.1186/s13023-020-1337-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in hereditary hemorrhagic telangiectasia severity

Abstract: Background: Gender differences in organ involvement and clinical severity have been poorly described in hereditary hemorrhagic telangiectasia (HHT). The aim of this study was to describe differences in the severity of HHT manifestations according to gender. Methods: Severity was measured according to Epistaxis Severity Score (ESS), Simple Clinical Scoring Index for hepatic involvement, a general HHT-score, needing for invasive treatment (pulmonary or brain arteriovenous malformations-AVMs-embolization, liver t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
(103 reference statements)
1
19
0
1
Order By: Relevance
“…In the present study we investigated the role of different genetic factors in the occurrence of HAVM in HHT patients. We confirmed the more severe hepatic involvement in females than in males, already observed in previous studies, with a growing proportion of women with the severity of hepatic disease (Table 1 ) [ 15 , 16 , 25 ]. One striking characteristic of HHT is the wide interfamilial and intrafamilial variability in the clinical expression of visceral AVMs.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study we investigated the role of different genetic factors in the occurrence of HAVM in HHT patients. We confirmed the more severe hepatic involvement in females than in males, already observed in previous studies, with a growing proportion of women with the severity of hepatic disease (Table 1 ) [ 15 , 16 , 25 ]. One striking characteristic of HHT is the wide interfamilial and intrafamilial variability in the clinical expression of visceral AVMs.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, important parameters that may affect bleeding such as clinical variants of HHT, type of mutations, as was previously shown by Lesca et al [ 35 ], family relations of the participants, age, and gender were not evaluated. Notably, we had female predominance and, although recent publication did not find a difference in epistaxis frequency between genders [ 36 ], a match for gender should be considered in a larger study.…”
Section: Discussionmentioning
confidence: 91%
“…Larger studies comparing HHT patients with and without underlying pathogenic variants in HHT-associated genes are needed to further explore this finding. Overall, these data suggest that The data regarding genotype and prevalence of pulmonary and cerebral AVMs varies between studies, with some studies demonstrating an association while others do not [6,13,14,29,31,32,34]. This discrepancy between studies may be related to racial/ethnic differences in the study populations, study methodologies, and the impact of co-existing gene variants that modify HHT biology [35,36].…”
Section: Discussionmentioning
confidence: 93%
“…Our data do not demonstrate an association between gender or genotype and prevalence of pulmonary or brain AVMs; however, this may be due to lack of sufficient numbers, especially within the brain AVM cohort. Recent data from Mora-Lujan et al has demonstrated an association between female gender and increased risk of hepatic AVMs [31]. Unfortunately, our data set did not include information regarding hepatic AVM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation